Dual therapy with allicin and metformin provides superior cardioprotection against doxorubicin-induced cardiotoxicity in rats compared to monotherapy - Mojamel, Mohammed; Al-Mahbashi, Hassan; Al-Nabehi, Afif (Frontiers in Pharmacology, 2026)
BackgroundDoxorubicin is a widely used chemotherapeutic agent; however, its clinical utility is limited by dose-dependent cardiotoxicity. Existing cardioprotective strategies are insufficient, showing that there is a need for safer and more effective alternatives.ObjectivesThis study evaluated the cardioprotective effects of metformin and allicin, individually and in combination, against doxorubicin-induced cardiotoxicity in rats.MethodsFifty adult male Wistar albino rats were randomized into five groups (n = 10 each): The control group was administered normal saline (2 mL/kg, intraperitoneally, on days 7, 14, and 21); the DOX-only group received doxorubicin (6 mg/kg, intraperitoneally, on days 7, 14, and 21; cumulative dose 18 mg/kg); the DOX + Allicin group was given allicin (40 mg/kg/day, orally), the DOX + Metformin group received metformin (300 mg/kg/day, orally), and the DOX + Allicin+ Metformin group received both agents at these doses. Treatments were given orally once daily for 21 days. On day 22, blood samples and cardiac tissues were collected for biochemical and histopathological evaluation. Parameters assessed included body and heart weights, serum cardiac biomarkers (CK-MB, LDH, cTn I), antioxidant defenses (GSH, CAT, GPx, SOD), and oxidative stress indices (MDA, NO).ResultsBoth allicin and metformin significantly attenuated DOX-induced elevation of cardiac enzymes, with greater protection observed under combined therapy. Antioxidant markers (GSH, GPx, SOD, CAT, NO) increased significantly, whereas MDA levels decreased. Dual treatment produced superior effects compared to either agent alone, a finding further supported by marked histopathological improvement in cardiac tissues.ConclusionMetformin and allicin each conferred significant cardioprotection against doxorubicin-induced cardiotoxicity, evidenced by the restoration of cardiac enzymes, reduction of oxidative stress, and improvement in myocardial histoarchitecture. Notably, combined therapy produced greater biochemical and structural recovery than either monotherapy, highlighting its enhanced overall cardioprotective efficacy.